2012
DOI: 10.3109/00016489.2012.663932
|View full text |Cite
|
Sign up to set email alerts
|

Lateral semicircular canal plugging with endolymphatic sac decompression as new surgical treatment for intractable Meniere's disease

Abstract: The attack of Meniere's disease was completely controlled and the hearing threshold did not change after the surgery for 2 years. Obliteration of the horizontal canal was confirmed by MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Similar conclusions can be drawn for diuretics, also prescribed by 63% of the surgeons in the UK for Ménière's disease [Smith et al, 2005] despite the lack of evidence of their effectiveness and the important burden of evidence of their side effects, particularly during long-term treatment [Pirmohamed et al, 2004;Pirodda et al, 2011]. Endolymphatic sac surgery also seems not to have any significant effects in the majority of the treated population with Ménière's disease, although new techniques have shown some positive results [Goto et al, 2012], but again, its side effects may be underestimated [Xu et al, 2011]. Intratympanic steroids, despite the small population included in the trial (only 22 individuals), have been shown to be an effective treatment, with improvement of the frequency and severity of vertigo lasting for over 2 years [Phillips and Westerberg, 2011].…”
Section: Discussionsupporting
confidence: 52%
“…Similar conclusions can be drawn for diuretics, also prescribed by 63% of the surgeons in the UK for Ménière's disease [Smith et al, 2005] despite the lack of evidence of their effectiveness and the important burden of evidence of their side effects, particularly during long-term treatment [Pirmohamed et al, 2004;Pirodda et al, 2011]. Endolymphatic sac surgery also seems not to have any significant effects in the majority of the treated population with Ménière's disease, although new techniques have shown some positive results [Goto et al, 2012], but again, its side effects may be underestimated [Xu et al, 2011]. Intratympanic steroids, despite the small population included in the trial (only 22 individuals), have been shown to be an effective treatment, with improvement of the frequency and severity of vertigo lasting for over 2 years [Phillips and Westerberg, 2011].…”
Section: Discussionsupporting
confidence: 52%
“…They observed a resolution of vertigo episodes in 64.5% of their patients, with improved hearing in 14.8% of them. Goto et al17 and Kim et al18 reported similar results for vertigo control in recent years.…”
Section: Review Of the Literaturementioning
confidence: 61%
“…Endolymphatic sac decompression can minimize potential inner ear damage, including aggravation of endolymphatic effusions, due to increased pressure in the long-term resulting from plugging of semicircular canals ( 31 ). TSCO can block signal conduction in the vertigo conduction pathway and enhance vertigo control.…”
Section: Discussionmentioning
confidence: 99%